Extracción de aceite a partir de microalgas obtenidas de la laguna El Estanco, en San Andrés de sotavento - Colombia - Escobar, Karol Fuentes; Bonilla, Julián Olivera; Chaparro, Adela Rodríguez (KnE Engineering, 2018)
The objective of this research is to extract oil from the microalgae obtained in the lagoon El Estanco, located in San Andrés de Sotavento, Colombia, using the modified Bligh & Dyer method, with two types of solvents For chloroform + methanol and hexane. The results obtained with solvent extraction chloroform + methanol provided the largest volume of extracted oil, a comparison with hexane. Keywords: Oil, Extraction, Microalgae.